Fabrication, characterization and evaluation of β-elemene nanoparticles for anti-cancer treatment - Zhao, Xi (2020)
Cancer is one of the leading causes of death worldwide, causing about 9.6 million deaths in 2018. Systemic chemotherapy is a widely used treatment against cancer. However, it is difficult for chemotherapeutic to reach the specific tumour tissues, which can result in some side effects in normal healthy tissues. With the development of nanotechnology in medical area, it becomes possible to deliver drugs to target region by using nanoparticles. Low-density lipoprotein is an excellent example of nanocarrier system for hydrophobic materials. According to some studies, LDL uptake by cancer cells are higher than normal cells.